Factorial methods in the analysis of spatial data. An application to the 2012 agricultural census data for the characterization of the provinces of Peru - Cambillo Moyano, Emma Norma (2016)
The Peruvian provinces were tipified by factorial methods with incorporating geo-referenced data with information from the 2012 National Agricultural Census. Were determined three indicators : Intensity of agricultural activity, commercialization of agricultural production, and use of water sources for irrigation; The use of the Moran Index helped identify provinces with similar agricultural characteristics. The results could be used to route some objectives of the strategic plan of the agricultural sector, and monitor policies of institutional development in the sector. The informatión also could be useful for designing development plans that meet the needs of the agricultural sector and to have a clear idea of the agricultural characteristics of all the provinces of Peru, with the object to orient the investment in the country.